Pengaruh Latihan Depth Jump dan Knee Tuckjump terhadap Peningkatan Vertical Jump pada Siswa Putra Ekstrakurikuler Voli di SMAN 2 Ngadirojo Pacitan - Hadipurwa, Dwi Angga, Dwi Rosella K, S,Fis., M.Fis, Arif Pristianto, SSt.FT.,M.Fis (2016)
Vertical jump is one of the most important elements in the sport of volleyball. Vertical jump is a complex process that involves strength, speed and endurance of the muscles of the leg. Good vertical jump is not obtained by instant but by a physical exercise that is able to activate the muscle fibers so that muscle power, speed and good durability. One method of exercise that can improve one's vertical jump is to perform plyometrics exercises. In this study, researchers apply plyometrics training methods depth knee tuck jump and jump to the increased vertical jump at SMAN 2 Ngadirojo Pacitan. Samples in this study were all male students at SMAN 2 Ngadirojo who joined the extracurricular volleyball, amounting to 22 respondents, then from 22 respondents were divided into two groups, with a treatment depth jump as much as 11 respondents, and group with the treatment knee tuck jump as much as 11 respondents. This research method using quasi-experimental approach, with a design in the form of pre-test and post-test two group design. The test effect of using the wilcoxon test to determine the effect of pre and post test while using a different test of Mann Whitney. The results showed a depth jump plyometrics exercises influence on the vertical jump with the value 0.007, where as the knee tuck jump plyometrics exercises show the effect on vertical jump with the value 0.003, so there is a difference between the depth jump plyometrics exercises and knee tuck jump to increase vertical jump in volleyball extracurricular student at SMAN 2 Ngadirojo with the value 0.040